The influence of financial and legal institutions on firm size - Beck, Thorsten; Demirgüç-Kunt, Aslı; Maksimovic, Vojislav (Journal of Banking & Finance, 2006)
Theory does not predict an unambiguous relationship between a country’s financial and legal institutions and firm size. Using data on the largest industrial firms for 44 countries, we find that firm size is positively related to financial intermediary development, the efficiency of the legal system and property rights protection. We do not find any evidence that firms are larger in order to internalize the functions of the banking system or to compensate for the general inefficiency of the legal system.